Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2147/ccid.s153905
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging efficacy of melatonin-based day and night creams: a randomized, split-face, assessor-blinded proof-of-concept trial

Abstract: BackgroundSkin is a complete and independent melatoninergic system. At the skin level, melatonin (Mel) acts as a relevant antioxidant and cytoprotective substance. Topical application of Mel is considered meaningful, since it can easily penetrate the stratum corneum. Exogenous Mel can be expected to represent a potent antioxidative defense system against skin aging mechanisms. Day and night creams containing Mel, carried in lipospheres (Melatosphere™), have been developed (Nutriage SPF 30 day cream and Nutriag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
1
39
0
2
Order By: Relevance
“…There is a wealth of literature on antioxidants and anti‐aging products, and multiple in vitro and in vivo studies of the effects of melatonin; however, very few published clinical studies have assessed the effects of a finished anti‐aging product containing melatonin. A recent study by Milani et al involving a twice‐daily regime of 0.1% melatonin‐based creams reported a significant reduction in crow's feet wrinkles of −15% on dermatologist clinical scoring assessment, but on instrumental assessment (profilometry) the differences did not reach statistical significance. The present study adds to this evidence of a clinical effect from melatonin‐based products, as we also found significant wrinkle reductions on clinical scoring (−5% at 1 month; −11% at study end) but in this case the differences also reached statistical significance on instrumental assessment, after just 1 month of use (Dermatop assessment).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There is a wealth of literature on antioxidants and anti‐aging products, and multiple in vitro and in vivo studies of the effects of melatonin; however, very few published clinical studies have assessed the effects of a finished anti‐aging product containing melatonin. A recent study by Milani et al involving a twice‐daily regime of 0.1% melatonin‐based creams reported a significant reduction in crow's feet wrinkles of −15% on dermatologist clinical scoring assessment, but on instrumental assessment (profilometry) the differences did not reach statistical significance. The present study adds to this evidence of a clinical effect from melatonin‐based products, as we also found significant wrinkle reductions on clinical scoring (−5% at 1 month; −11% at study end) but in this case the differences also reached statistical significance on instrumental assessment, after just 1 month of use (Dermatop assessment).…”
Section: Discussionmentioning
confidence: 94%
“…Melatonin also acts synergistically with vitamins C and E, protecting against ultraviolet‐induced skin erythema . Despite substantial evidence on its antioxidant potential, few clinical studies have investigated its topical anti‐aging effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, melatonin has been used in cosmetic creams. For example, melatonin-based creams significantly improved skin tonicity and skin hydration in women, with a significant reduction in skin roughness, supporting the skin anti-aging effect of this molecule when applied topically [101]. Several cosmetic lines containing synthetic melatonin are marketed, but not containing phytomelatonin.…”
Section: Resultsmentioning
confidence: 93%
“…Topical application of Mel is considered meaningful, since it can easily penetrate the stratum corneum 14 . A recent clinical trial has shown that topical Mel improves clinical signs of skin aging 15 .…”
Section: Introductionmentioning
confidence: 99%